Seed Accelerator Meet 2.0 - Nayak, Swati; Hossain, Sk Mosharaf; Mohapatra, Subhasmita; Tyagi, Neeraj Kumar; Nath, Anirban; Singh, Vikas Kumar; Shukla,Sarvesh; Rout, Dillip Kumar; Swain, Girija Prasad; Venkateshwarlu, Challa; Mall, Ashish (International Rice Research Institute, 2025)
The Seed Accelerator Meet 2.0, organized by the International Rice Research Institute (IRRI) at the ICRISAT campus in Hyderabad in May 2025, served as a multi-stakeholder platform to accelerate varietal turnover and strengthen rice seed systems in India. Anchored in IRRI’s market-driven One Rice Breeding and Seed System Strategy, the workshop brought together ICAR-ATARIs, state seed corporations, private seed companies, FPOs, and NGOs to address persistent gaps between varietal innovation and farmer-level adoption. Evidence from large-scale on-farm trials conducted across multiple states and market segments demonstrated the superior performance of several new rice varieties, reinforcing the need for demand-led varietal positioning and early-generation seed (EGS) linkages. Discussions highlighted systemic challenges related to breeder seed access, varietal data sharing, storage infrastructure, policy incentives, and market alignment, while emphasizing inclusive, decentralized seed production models. Special focus was given to climate-resilient, biofortified, and specialty rice segments. Overall, the meet reinforced the importance of coordinated public–private–community partnerships, data-driven decision-making, and institutional convergence for building resilient, inclusive, and responsive rice seed systems in India.